PERBANDINGAN PENDIDIKAN ISLAM DENGAN PENGENALAN PRINSIP-PRINSIP DAN ASUMSI-ASUMSI MULTIKULTURAL PADA MASA NABI, SAHABAT DAN KEEMASAN ISLAM - Yuni Hana Lestari; Zubaidi Zubaidi; Alfauzan Amin; Hery Noer Aly (Smart Education, 2025)
A comparison between Islamic educational practices and the emergence of multicultural principles during three major phases of Islamic civilization: the era of the Prophet Muhammad, the period of the Companions, and the Islamic Golden Age. Using a qualitative-historical approach, this study analyzes classical Islamic texts, historical sources, and contemporary academic works. Findings reveal that Islamic education has been inherently multicultural, emphasizing tolerance, justice, equality, pluralism, and intellectual openness. During the Prophet’s time, multicultural values were implemented through the teaching of Qur’anic ethics and the Charter of Medina. The Companions institutionalized these values through governance and public education. Meanwhile, the Islamic Golden Age demonstrated the highest multicultural expression through knowledge translation, cross-cultural academic collaboration, and institutional learning spaces such as Bayt al-Hikmah. This research concludes that Islamic education historically practiced multicultural frameworks long before the formation of modern multicultural educational theories.